Persistence of Symptoms After Discharge of Patients Hospitalized Due to COVID-19 - Wu, Lili; Wu, Yongxin; Xiong, Haiyan; Mei, Biqi; You, Tianhui (Frontiers in Medicine, 2021)
Many patients who had coronavirus disease 2019 (COVID-19) had at least one symptom that persisted after recovery from the acute phase of this disease. The most common persistent symptoms are fatigue, cough, dyspnea, chest pains, chest tightness, joint pain, muscle pain, loss of taste or smell, hair loss, sleep difficulties, anxiety, and depression. Some of the less common persistent symptoms are skin rash, decreased appetite, sweating, inability to concentrate, and memory lapses. In addition to these general symptoms, some patients experience dysfunctions of specific organs, mainly the lungs, heart, kidneys, and nervous system. This article reviews the epidemiology and long-term health outcomes of adults with COVID-19 after hospital discharge, many of whom were discharged with impaired physical functions. We suggest that the early initiation of rehabilitation during the post-hospitalization stage, and active rehabilitation training and targeted interventions for patients with respiratory, physical, or mental disorders. Prompt rehabilitative care of these patients may improve their recovery from physical, immune, and mental health symptoms.